Intrinsic capacity, functional and psychosocial aspects of older adults participating in a multicomponent physical exercise program - Felipe, Sarah Giulia Bandeira; Printes, Clarisse Bielh; Brauner, Fabiane de Oliveira; Sato, Douglas Katusohi; Baptista, Rafael Reimann (Frontiers in Aging, 2025)
IntroductionIn 2015, the WHO introduced intrinsic capacity (IC) as a health indicator with five domains to promote healthy aging. Multicomponent exercise programs are recommended to enhance IC, but research in Brazil on their comprehensive impact is limited. This study aimed to evaluate the effects of such a program on IC, functional, and psychosocial aspects in older adults.MethodsThis pre- and post-study assessed older adults in Brazil enrolled in a multicomponent training program, evaluating IC as the main outcome using specific tests for each domain. Inclusion criteria were: aged 60+, completing assessments in five domains, attending the program at least twice a week, and participating in two exercise modalities per session for 90 min. Exclusion criteria included: history of stroke, Parkinson’s or Alzheimer’s, recent hand, hip, or knee surgery, or absence for more than 15 consecutive days. A total of 43 older adults were evaluated, and the score was calculated by summing the results of the five domains, yielding a total score ranging from 0 to 10 points. Subsequently, participants underwent a 12-week intervention involving multicomponent exercises and were reassessed.ResultsAfter 12 weeks of intervention, there was a significant reduction in the proportion of participants with low IC, from 7.0% to 0.0%, and an increase in those with high IC, from 4.7% to 20.0% (p = 0.018). Improvements were seen in cognitive aspects, locomotor dimension (p < 0.001), vitality (p = 0.045) and functional classification (p < 0.001), with the greatest effect in the locomotor domain (es = 1.12). Significant gains were also observed in perceived health, quality of life, and physical activity (p < 0.002; p < 0.004; p < 0.001). Body composition showed improvements, including reduced body fat percentage, increased muscle mass, and better fat classification (p < 0.001), along with reductions in waist and abdominal circumferences (p < 0.001; p = 0.001).ConclusionThe multicomponent exercise program demonstrated a positive influence on composite IC, including functional and psychosocial aspects. These findings highlight the critical role of tailored and supervised exercise interventions in enhancing both physical and psychosocial dimensions of health, contributing to healthier aging trajectories.